Exosomal MicroRNAs Mediating Crosstalk Between Cancer Cells With Cancer-Associated Fibroblasts and Tumor-Associated Macrophages in the Tumor Microenvironment - Su, Tong; Zhang, Panpan; Zhao, Fujun; Zhang, Shu (Frontiers in Oncology, 2021)
Exosomes are small extracellular vesicles containing diverse bioactive molecules. They play essential roles in mediating bidirectional interplay between cancer and stromal cells. Specific elements are selected into different types of exosomes via various mechanisms, including microRNAs (miRNAs), a subset of noncoding RNA that could epigenetically reprogram cells and modulate their activities. Cancer-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs) are two major types of stromal cells inhibiting immune response and facilitating tumor progression. Notably, accumulated studies provided critical evidence regarding the significance of exosomal miRNA–mediated intercellular crosstalk between cancer cells with TAMs and CAFs for tumor progression. This study aimed to summarize the current knowledge of cell–cell interactions between stromal and cancer cells conveyed by exosome-derived miRNAs. The findings might help find effective therapeutic targets of cancer.